Mitral Valve Plasty During Correction of Combined Mitral-Aortic Valve Diseases - Vitovskiy, R.; Bolshak, O.; Boukarim, V.; Bakhovska, Yu.; Popov, V. (Ukrainian Journal of Cardiovascular Surgery, 2020)
The aim. To study reconstructive operations on the mitral valve (MV) combined with aortic valve replacement (AVR) for combined mitral-aortic valve defects (CMAVD). Materials and methods. The study included 1690 patients with CMAVD who underwent surgical treatment at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine for the period from 01/01/2006 to 01/01/2020. Of these, 429 (23.4%) patients underwent MV reconstruction with AVR. The following valve-sparing procedures were performed: – application of annuloplasty ring: 123 (28.7%); – MV suture annuloplasty: 137 (31.9%); – open mitral commissurotomy: 47 (11.0%); – open mitral commissurotomy + leaflet plication: 4 (0.9%); – application of autopericardial patch on the MV leaflet: 7 (1.6%); – alfieri procedure (MV bicuspidalization): 34 (7.9%); – mitral valve debridgment 12: (2.8%); – plasty with autopericardial patch: 18 (4.2%); – removal of vegetation from MV structures : 7 (1.6%); – resection of MV leaflets with addition of suture annuloplasty: 19 (4.4%); – resection of MV leaflets with addition of an annuloplasty ring: 21 (4.9%). Results. Fatal complications occurred in 4 cases due to heart failure (n = 2) and multiple organ failure (n = 2). Hospital mortality in AVR with MK plasticity MV plasty was 0.9%, which once again emphasizes the importance of traumatic intervention compared with combined mitral-aortic prosthetics, where mortality is 3 times higher. It decreased from 2.9% (2006–2012, n = 128) to 0.3% (2013–2019, n = 301), which indicates the effectiveness of the method with a significant increase in the number of operated patients. After correction, MV regurgitation decreased from +2.4 ± 0.3 to +0.4 ± 0.03. Coaptation of the sash Mk MV leaflets after correction was 7.4 ± 0.6 mm. At the hospital stage there was a decrease in the diastolic peak gradient on the MV from 19.4 ± 4.8 mm Hg to 6.4 ± 0.8 mm Hg. In the remote period, 82.6% of the discharged patients (n = 351) in the period of were followed for 9.3 ± 2.4 years. Better indicators were noted in group of patients with functional class III than those with functional class IV (p <0.05). Fatal outcomes due to thromboembolic complications (n = 29) were caused by the presence of a mechanical aortic prosthesis and partial non-compliance with the protocol of anticoagulant therapy. Unsatisfactory result in the group with changes in the MV was due to the activity of the rheumatic process and progressive heart failure with prolonged atrial fibrillation (n = 37). The etiology of the defect affected the long-term outcome. The activity of the rheumatic process in patients with functional class IV determined changes in the MV leaflets in the long term and worsened the result. MV regurgitation increased from +0.08 ± 0.03 (5 years after surgery) to +1.2 ± 0.3 (10 years after surgery). In the long term there was an increase in the diastolic peak gradient on the MV from 9.4 ± 0.4 mm Hg (5 years after surgery) to 13.4 ± 3.2 mm Hg (10 years after surgery). MV replacement was performed in 4 patients 6, 9, 10, 11 years after surgery. Conclusions. Given the available clinical experience, it is advisable to recommend reconstructive interventions on the MV to correct CMAVD and improve the level of survival and stability of good results.